Cholecystectomy in a trial of adjuvant chemotherapy after pancreatic cancer resection - Neoptolemos, John P.; Stocken, Deborah D.; Büchler, Markus W. (The journal of the American Medical Association, 2010)
In Reply: In response to Dr Dubecz and colleagues, when we devised the ESPAC-3 trial, we specified the type of pancreatic resection in the protocol according to an internationally agreed classification. The recommendation was that “the gallbladder is dissected in continuity with the main extrahepatic bile duct,” ensuring inclusion of the associated lymph nodes within the hepatoduodenal ligament. Thus, we would agree with the writers.Nevertheless, we are also aware that many pancreas surgery units do not follow this rule rigidly, and we wanted to capture the variation in practice to ascertain differences (if any) in survival. We therefore reported in our article the overall number of patients who underwent an en bloc cholecystectomy. Of note is that cholecystectomy was not associated with survival.